An over View of Forest Cover and Changes in Greening Pattern of Bundelkhand - Ramesha, M. N.; Dwivedi, V. K.; Krishnan, P. Ratha (Indian Forester, 2012)
Forest cover dynamics of Bundelkhand has been studied from 1971 to 2009. Madhya Pradesh part of Bundelkhand perhaps has ecologically near-suffice forest cover in southern districts viz., Chhatarpur, Damoh, Panna and Sagar (29.69 per cent GA) whereas Datia and Tikamgarh districts possess less than 10 per cent forest cover with declining trend. Uttar Pradesh part of Bundelkhand lies along the Yamuna river alluvial belt and is an intensively cultivated plain land. Forest cover in the region is very poor (6.6 per cent GA), five districts have less than 6 per cent GA under forest vegetation barring Chitrakoot and Lalitpur districts, having 18.14 and 11.31 per cent GA under forest respectively. There have been peaks and troughs in the long-term trend of forest area. All the districts had shown a trough of reduction in forest area from 1991 to 2003. Resource poor Bundelkhand region requires proper forestry initiatives to reverse dwindling forest area and tree cover to ensure small timber for agricultural implements, thorn and twigs for fencing and fuel wood for cooking.